The Silicon–Hydrogen Exchange Reaction: Catalytic Kinetic Resolution of 2-Substituted Cyclic Ketones - Zhou, Hui; Zhang, Pinglu; List, Benjamin (Synlett, 2021)
We have recently reported the strong and confined, chiral acid-catalyzed asymmetric ‘silicon−hydrogen exchange reaction’. One aspect of this transformation is that it enables access to enantiopure enol silanes in a tautomerizing σ-bond metathesis, via deprotosilylation of ketones with allyl silanes as the silicon source. However, until today, this reaction has not been applied to racemic, 2-substituted, cyclic ketones. We show here that these important substrates readily undergo a highly enantioselective kinetic resolution furnishing the corresponding kinetically preferred enol silanes. Mechanistic studies suggest the fascinating possibility of advancing the process to a dynamic kinetic resolution.
Keywords: asymmetric catalysis; organocatalysis; enol silanes